2022
DOI: 10.1021/acsanm.2c03067
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride Composites with Gold and ZIF-67 Nanoparticles as Visible-Light-Promoted Catalysts for CO2 Conversion and Bisphenol A Degradation

Abstract: In this research work, the ZIF-67-coupled plasmonic-gold-incorporated porous g-C3N4 (ZIF/Au-PCN) nanocomposites have been successfully synthesized and utilized for the conversion of CO2 into useful products and Bisphenol A (BPA) decontamination. Compared to pristine PCN, the photocatalytic activities of the most active 3ZIF/1.5Au-PCN nanocomposite are enhanced by 8.0-fold for the conversion of CO2 and by 2.5-fold for BPA degradation. On the basis of our experimental results, it is verified that the porous natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The crystallinity of ZIF 67 was determined using XRD JDX0 362 (Japan) with Cu Kα radiation (wavelength 1.5418) with a scan angle range of 5° to 90° with a 40 kV acceleration voltage and 30 mA current. Figure 1 d depicts the patterns of ZIF-67 which are in accordance with the simulated pattern [ 28 ]. From all of the above characterization, we found that the product was pure phase ZIF-67 materials.…”
Section: Resultssupporting
confidence: 68%
“…The crystallinity of ZIF 67 was determined using XRD JDX0 362 (Japan) with Cu Kα radiation (wavelength 1.5418) with a scan angle range of 5° to 90° with a 40 kV acceleration voltage and 30 mA current. Figure 1 d depicts the patterns of ZIF-67 which are in accordance with the simulated pattern [ 28 ]. From all of the above characterization, we found that the product was pure phase ZIF-67 materials.…”
Section: Resultssupporting
confidence: 68%
“…2). [55][56][57][58][59][60] MOFs are a kind of relatively burgeoning porous crystalline organic-inorganic hybrid materials, which are assembled by the coordination effects of organic components and inorganic components. 61 There are many kinds of MOFs because of the diversity of organic and inorganic components (Fig.…”
Section: Sheng-hui Guomentioning
confidence: 99%
“…92,93 CO 2 is a stable molecule and requires catalysts to lower the dissociation energy of the C═O bonds. [94][95][96][97] Depending on the transfer of electrons and protons, CO 2 could be reduced to various products. Abundant unsaturated coordination sites of MoS 2 can act as active centers that interact with the target products to drive multistep reactions.…”
Section: Electrocatalysis Over Ultra-small Mosmentioning
confidence: 99%
“…Conversion of CO 2 into fuels is crucial for achieving environmental protection and addressing the energy crises 92,93 . CO 2 is a stable molecule and requires catalysts to lower the dissociation energy of the C═O bonds 94–97 . Depending on the transfer of electrons and protons, CO 2 could be reduced to various products.…”
Section: Catalysis Over Ultra‐small Mos2 For Renewable Fuel Productionmentioning
confidence: 99%